Evidence of multi-phase Cretaceous to Quaternary alkaline magmatism on Tore-Madeira Rise and neighbouring seamounts from 40Ar/39Ar ages. - Merle, R.; Jourdan, Fred; Marzoli, A.; Renne, P.; Grange, Marion; Girardeau, J. (Geological Society Publishing House, 2009)
The Tore-Madeira Rise is a seamount chain located 300 km off the Portugal and Morocco coastsattributed to hotspot activity. U-Pb ages of lavas from the northern and central Tore-Madeira Rise rangebetween 103 and 80.5 Ma whereas 40Ar/39Ar ages from the central and southern Tore-Madeira Rise yield ages ranging from 94.5 to 0.5 Ma. We performed new 40Ar/39Ar measurements to better understand the geodynamic history of the Tore-Madeira Rise. Plagioclase ages from the Bikini Bottom and Torillon seamounts suggest ages of .90 Ma and >60 Ma, respectively. Amphiboles from the Seine seamount yield an age of 24.0 +- 0.8 Ma. Biotites from lavas of the Ashton seamount give ages of 97.4 +- 1.1 Ma and 97.8 +- 1.1 Ma. The geochronological database available on the Tore-Madeira Rise has been filtered on statistical criteria to eliminate unreliable ages. The resulting database reveals three pulses of alkaline magmatism on the Tore-Madeira Rise at 103-80.5 Ma, at c. 68 Ma and between 30 Ma and the present. The magmatism was continuous from 103 Ma until c. 68 Ma and from c. 30 Ma until the present on the Tore-Madeira Rise, the surrounding seamounts and the Portugal coast. We suggest that the space-time distribution of this magmatism results from the interaction between a wide thermal anomaly emitting magmatic pulses and the complex motion of the Iberian plate.